Impacts of Fully Coupling Land Surface and Flood Models on the Simulation of Large Wetlands' Water Dynamics: The Case of the Inner Niger Delta. (25th May 2021) - Getirana, Augusto; Kumar, Sujay V.; Konapala, Goutam; Ndehedehe, Christopher E.
Abstract: It is known that representing wetland dynamics in land surface modeling improves models' capacity to reproduce fluxes and land surface boundary conditions for atmospheric modeling in general circulation models. This study presents the development of the full coupling between the Noah‐MP land surface model (LSM) and the Hydrological Modeling and Analysis Platform (HyMAP) flood model in the NASA Land Information System and its application over the Inner Niger Delta (IND), a well‐known hot‐spot of strong land surface‐atmosphere interactions in West Africa. Here, we define two experiments at 0.02° spatial resolution over 2002–2018 to quantify the impacts of the proposed developments on simulating IND dynamics. One represents the one‐way approach for simulating land surface and flooding processes (1‐WAY), that is, Noah‐MP neglects surface water availability, and the proposed two‐way coupling (2‐WAY), where Noah‐MP takes surface water availability into account in the vertical water and energy balance. Results show that accounting for two‐way interactions between Noah‐MP and HyMAP over IND improves simulations of all selected hydrological variables. Compared to 1‐WAY, evapotranspiration derived from 2‐WAY over flooding zones doubles, increased by 0.8 mm/day, resulting in an additional water loss rate of ∼18, 900 km 3 /year, ∼40% drop of wetland extent during wet seasons, and major improvement in simulated water level variability at multiple locations. Significant soil moisture increase and surface temperature drop were also observed. Wetland outflows decreased by 35%, resulting in a substantial Nash‐Sutcliffe coefficient improvement, from −0.73 to 0.79. It is anticipated that future developments in water monitoring and water‐related disaster warning systems will considerably benefit from these findings. Plain Language Summary: Many hydrological modeling systems are composed of land surface models (LSMs) capable of representing vertical land surface‐atmosphere interactions, and flood models capable of simulating the lateral redistribution of surface waters across a prescribed river network and floodplains. These models are oftentimes one‐way coupled, meaning that surface waters are neglected in the vertical water and energy balance. This study presents a generalized approach for the two‐way coupling (i.e., surface waters are taken into account in the vertical water and energy balance) between the Noah‐MP LSM and the HyMAP flood model. The proposed approach is tested over the Inner Niger Delta (IND), a well‐known hot‐spot of strong land surface‐atmosphere interactions in West Africa. To quantify the impact of the proposed development on the spatiotemporal variability of simulated hydrological variables, we performed two model experiments, one representing the one‐way approach, i.e., Noah‐MP neglects surface waters, and the proposed two‐way coupling, where surface water availability is taken into account. Results show that accounting for two‐way interactions between Noah‐MP and HyMAP over IND improves simulations of all selected hydrological variables. The generalized approach proposed here could be an asset to existing water monitoring systems and easily replicated over different domains or at the global scale. Key Points: The full coupling of land surface and flood models in NASA's Land Information System is described and evaluated over the Inner Niger Delta Increased evapotranspiration resulted in 18, 900 km 3 /year water loss to the atmosphere, decreasing wetland outflows by 35% and extent by 40% Compared to an uncoupled system, the proposed implementation resulted in substantial improvements of all selected hydrological variables